Rosales - Aguilar, Erick Dasig (Philippine humanities review = Rebyu ng Arte at Literatura ng Pilipinas.)
"... graphic depiction of child abuse, a moving story of how a child is initiated into life's sad realities when he witnesses the violence committed by his uncle against his grandmother. The boy's summer vacation in what he thought was an idyllic province, becomes a painful lesson on cruelty as he himself becomes the target of his uncle. Set in Rosales, Pangasinan, the story successfully weaves Ilokano words with Filipino, which helps highlight the disturbing situation of the protagonist." -- Introduction